FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BIDAN PADA PELAYANAN ANTENATAL CARE DI PUSKESMAS SEKOTA PALEMBANG TAHUN 2014 - Wargustini Wargustini (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2014)
ABSTRACK This study aimed to determine the knowledge, motivation, leadership, incentives / rewards, and education with the performance of midwives in Antenatal Care Services (ANC) at health centers in the country Palembang, this study uses observational analytic study design "cross sectional" with 48 midwives sample using the formula, by conducting interviews and questionnaires. There are 15 respondents have less knowledge has an 31.25% lower performance. Results obtained by chi-square test p-value = 0.04 (p <0.05) and Rφ = 0.288 means that there is a connection with the performance of midwife knowledge, the closeness of the relationship is low, motivation midwives obtained value ρ = 0.017 and Rφ = 0.466 means that there is a relationship the performance of average -midwife with the relationship, clinic leaders leadership values obtained ρ = 0.00 and Rφ = 0.28 means that there is a relationship with the midwives' work closeness of the relationship is low. Chi-square test results obtained by the value of the incentive factor ρ = 0.019 = 0.328 declared value Rφ no relationship with the midwives' work closeness of the relationship is average. Factors education obtained ρ = 0.021 and the value of Rφ = 0.041 means that there is a relationship with the midwives' work closeness of the relationship being. Four chief centers are expected to consider factors - factors related to the performance of midwives that knowledge, motivation, leadership, incentives, and education. ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor pengetahuan, motivasi kerja, kepemimpinan, insentif / imbalan, dan pendidikan yang berhubungan dengan kinerja bidan pada pelayanan Antenatal Care ( ANC ) di Puskesmas Sekota Palembang, penelitian ini menggunakan penelitian observasi analitik dengan rancangan “cross sectional study” dengan jumlah sampel 48 bidan dengan menggunakan rumus, dengan melakukan wawancara dan kuesioner. Terdapat 15 responden memiliki pengetahuan kurang 31,25 % memilki kinerja rendah. Hasil uji chi-square diperoleh nilai p=0,04 ( p< 0,05) dan Rφ = 0,289 berarti ada hubungan pengetahuan dengan kinerja bidan, dengan keeratan hubungan rendah, motivasi bidan diperoleh nilai ρ=0,017 dan Rφ=0,466 berarti ada hubungan dengan kinerja bidan dengan keeratan hubungan sedang, kepemimpinan pemimpin puskesmas diperoleh nilai ρ=0,00 dan Rφ = 0,28 berarti ada hubungan dengan kinerja bidan dengan keeratan hubungan rendah. Hasil uji chi-square faktor insentif diperoleh nilai ρ = 0,019 nilai Rφ = 0,328 menyatakan ada hubungan dengan kinerja bidan dengan keeratan hubungan rendah. Faktor pendidikan diperoleh nilai ρ = 0,021 dan Rφ = 0,41 berarti ada hubungan dengan kinerja bidan dengan keeratan hubungan sedang. Diharapkan keempat kepala puskesmas memperhatikan faktor – faktor yang berhubungan dengan kinerja bidan yaitu pengetahuan, motivasi kerja, kepemimpinan, insentif, dan pendidikan.